The relationship of Bradykinin B₂ receptor gene variation with obesity, hypertension and lipid variables in obese patients - Bakır, Nur; Bozkuş, Hasan Mert; Koldemir Gündüz, Meliha; Çağatay, Penbe; Taşkın, Mustafa; Süsleyici Duman, Belgin (My University, 2014)
Objective. This study examined the association of C-58T genotypes with obesity/hypertension related parameters and serum lipids in obese (n=108) and non-obese (n=80) patients. Materials and methods. Bradykinin receptor (B2 R) C-58T genotypes were determined by PCR–RFLP. Results. B2 R gene C-58T frequencies for T/T (homozygous wild type), T/C (heterozygous) and C/C (homozygous polymorphic) genotypes for obese and non-obese patients were respectively: 36.1%, 37.5%; 45.4%, 52.5% and 18.5%, 10%. Obese patients using diuretic medication had lower C/C genotype frequency compared to T/T and T/C genotypes. Total cholesterol (T-Chol) (p=0.035) levels were found to be associated with B2 R C-58T polymorphism, where the T/T genotype had higher total cholesterol levels compared to the T/C genotype in obese patients. Non-obese patients using oral antidiabetic medication had higher C/C genotype frequency than that of T/T and T/C genotypes. Waist circumference (p=0.016) and diastolic blood pressure (p=0.01) levels were elevated in the non-obese subjects with the C/C genotype compared to T/C and T/T. Conclusion. Although B2 R C-58T gene polymorphism was not found to be effective on obesity with logistic regression analysis in the whole study population in obese subjects, the T-Chol decreasing effect of the B2 R gene C allele and the higher waist circumference measurements in the non-obese subjects may indicate there may be a link between B2 R gene C-58T polymorphism and obesity in study populations of higher numbers

Objective. This study examined the association of C-58T genotypes with obesity/hypertension related parameters and serum lipids in obese (n=108) and non-obese (n=80) patients. Materials and methods. Bradykinin receptor (B2 R) C-58T genotypes were determined by PCR–RFLP. Results. B2 R gene C-58T frequencies for T/T (homozygous wild type), T/C (heterozygous) and C/C (homozygous polymorphic) genotypes for obese and non-obese patients were respectively: 36.1%, 37.5%; 45.4%, 52.5% and 18.5%, 10%. Obese patients using diuretic medication had lower C/C genotype frequency compared to T/T and T/C genotypes. Total cholesterol (T-Chol) (p=0.035) levels were found to be associated with B2 R C-58T polymorphism, where the T/T genotype had higher total cholesterol levels compared to the T/C genotype in obese patients. Non-obese patients using oral antidiabetic medication had higher C/C genotype frequency than that of T/T and T/C genotypes. Waist circumference (p=0.016) and diastolic blood pressure (p=0.01) levels were elevated in the non-obese subjects with the C/C genotype compared to T/C and T/T. Conclusion. Although B2 R C-58T gene polymorphism was not found to be effective on obesity with logistic regression analysis in the whole study population in obese subjects, the T-Chol decreasing effect of the B2 R gene C allele and the higher waist circumference measurements in the non-obese subjects may indicate there may be a link between B2 R gene C-58T polymorphism and obesity in study populations of higher numbers
Keywords: B R C-58T polymorphism, PCR, Obesity, Serum lipids, Oral antidiabetic